Effectiveness of “Heni’s Dental Flannel Book” On Improving Dental Health Care among Early Childhood - Nugraheni Widyastuti; Diyah Fatmasari; Masrifan Djamil (International Journal of Nursing and Health Services (IJNHS), 2020)
One of the factors causing dental caries is the lack of children's knowledge resulting in a lack of awareness of children maintaining dental hygiene. To increase children's knowledge can promote dental health through child oral health education and mouth. The use of media is still less effective in health education that has been running. Therefore the need for innovation and development is to use media innovation "Heni's Dental Flannel Book." The study aimed to develop "Heni's Dental Flannel Book" media as a health education book and the effectiveness "Heni's Dental Flannel Book" for increasing the dental health care of Early Childhood Education Programs. Research and Development (R & D), there are ten stages of research, namely: information gathering, design models, validation expert, revision, product trial (Pre experiment with one group pre-test post-test, a sample of 15 children), modification, application trial (Quasi-experimental with pre-test and post-test nonequivalent control group design, a sample of 20 children in the intervention group and 20 children in the control group, final product revision, production of a product. Data were tested using ANOVA, Shapiro Wilk, Wilcoxon test, Mann-Whitney test. "Heni's Dental Flannel Book" is useful as an effort to increase dental and oral health care for Early Childhood Education Programs, as indicated by a p-value<0.001. Children's knowledge is characterized by a p-value<0.000, a child's attitude is shown by a p-value <0.000. There is a difference in the effectiveness of smart dental books and flipchart in increased dental and oral health care for children with a p-value of <0.000. “Heni’s Dental Flannel Book” effectively improve children's knowledge and attitudes